STROCSS 2021: Strengthening the reporting of cohort, cross-sectional and case-control studies in surgery. (December 2021) - Mathew, Ginimol; Agha, Riaz; ,; Albrecht, Joerg; Goel, Prabudh; Mukherjee, Indraneil; Pai, Prathamesh; D'Cruz, Anil K.; Nixon, Iain J.; Roberto, Klappenbach; Enam, Syed Ather; Basu, Somprakas; et al.
Abstract: Introduction: Strengthening The Reporting Of Cohort Studies in Surgery (STROCSS) guidelines were developed in 2017 in order to improve the reporting quality of observational studies in surgery and updated in 2019. In order to maintain relevance and continue upholding good reporting quality among observational studies in surgery, we aimed to update STROCSS 2019 guidelines. Methods: A STROCSS 2021 steering group was formed to come up with proposals to update STROCSS 2019 guidelines. An expert panel of researchers assessed these proposals and judged whether they should become part of STROCSS 2021 guidelines or not, through a Delphi consensus exercise. Results: 42 people (89%) completed the DELPHI survey and hence participated in the development of STROCSS 2021 guidelines. All items received a score between 7 and 9 by greater than 70% of the participants, indicating a high level of agreement among the DELPHI group members with the proposed changes to all the items. Conclusion: We present updated STROCSS 2021 guidelines to ensure ongoing good reporting quality among observational studies in surgery. Highlights: STROCSS 2019 guidelines were updated through a DELPHI consensus exercise. High level of agreement was noted,  among the 42 DELPHI group members,  with the proposed changes to all the items. Updated STROCSS 2021 guideline is presented.